Pupils’ Risky Behavior in the Cyberspace During the Transition to Distance Education - MIČKOVÁ, HELENA; MIKOVÁ, JANA; NOVÁKOVÁ, ZDENKA; ŠMIDA, JAN (Journal of Education, Technology and Computer Science, 2023)
In connection with the covid pandemic and the closing of schools as anti-covid emergency measures in many countries, face-to-face teaching has moved to an online environment. The Ministry of Education, Youth and Sports of the Czech Republic has issued Methodological Recommendations for distance education realized online using software tools, the Internet, and digital technologies. The presented pilot study brought disturbing findings about online teaching, namely that respondents experienced threats during distance education, with some even being blackmailed. Three hundred fifteen respondents from elementary and secondary schools in the Czech Republic took part in the pilot study, which was realized via a questionnaire survey. At the same time, the pilot study points to other risks of online learning when transitioning to a distance form of education, which also presents several other risks in cyberspace.